Talasemia di Rumah Sakit Umum Pusat Dr. Sardjito Tahun 1986 - 1992 - Sunarto Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
Thalassemia is a great health problem in the affected countries, especially in the developing countries including Indonesia. There is no curative therapy up to now, while the supportive therapy should be done life4ong and such therapy brings many problems to the patients and an enormous burden to the community who should afford the health services.Ninety thalassemia syndrome, at Dr. Sardjito General Hospital during the period of 1986-1992 were retrospectively studied. The diagnosis was based on clinical manifestations, routine blood examination, HbF investigation either with alkali denaturation test or electrophoresis and on the evidence of trait in the parents. Thirty six patients had undergone molecular studies. Aspects of therapy were also studied.The study found that 57 and 33 patients were major thalassemia and thalassemia-hemoglobin E disease, respectively. There was no difference between major thalassemia and thalassemia-hemogolobin E disease in term of male and female proportion (p > .05), and on the level (p > .05). Foutty eight patients came from Yogyakarta Province, the rest came from various parts of Java, especially nearby Yogyakarta Province. Compared with the estimation, we conclude that many thalassemic patients had not yet been covered. The expenses for supportive therapy were so great, while most of the patients belonged to the middle to low sosioeconomic level, so that only 30-40% had come regularly for routine transfusion. Among the 36 patients who underwent molecular studies, 31 have been genotypically identified. Molecular diagnostic was aimed at the first step of prenatal diagnosis.Key words: thalassemia syndrome-thalassemia trait-blood transfusion-molecular study-prenatal diagnosis